Study of international development activities supportive of capacity building in the fisheries and oceans sectors of selected Commonwealth countries in four geographical regions : the Southern Africa Development community, Caribbean, South Africa ane West Africa (CIDA HullCA, 1995)
Focuses on the objective of achieving more efficient programming and sustainable development in the fisheries and oceans sectors.
DC